Novel GYS2 mutations in a Japanese patient with glycogen storage disease type 0a - Hiroyuki Iijima; Yasuhiko Ago; Ryoji Fujiki; Takaaki Takayanagi; Mitsuru Kubota (Molecular Genetics and Metabolism Reports, 2021)
Background: Glycogen storage disease type 0a (GSD 0a), caused by GYS2 mutations, has a broad phenotypic spectrum, mostly associated with hypoglycemia. This disease has been characterized by the inability to store glycogen in the liver, leading to no hepatomegaly. Although the prevention of hypoglycemia has been considered the first therapeutic goal, the long-term complications remain unclear. In addition, few studies summarized clinical or biochemical features or examined genotype-phenotype correlation. Case presentation: A 4-year-old Japanese boy was admitted to our hospital because of hypoglycemia. We suspected GSD 0a based on recurrent irritability episodes before feeding, fasting ketotic hypoglycemia, postprandial hyperglycemia/hyperlactatemia, and no hepatomegaly. Mutation analyses revealed novel mutations (p.His610fs and deletion of exons 8–10) in the GYS2 gene. At 5 years old, his growth and development are normal. Fasting symptoms and hypoglycemia remain controlled by dietary management. Review of literature: We summarized the clinical and biochemical features of 33 patients with GSD 0a and 27 different mutations in the GYS2 gene. Nonspecific fasting symptoms (lethargy, drowsiness, nausea, and irritability) were found in 39% of patients, whereas 41% were asymptomatic. All patients had a combination of fasting ketotic hypoglycemia and postprandial hyperglycemia/hyperlactatemia. Hepatomegaly and hepatic steatosis were observed in 12% and 73% of patients. There was no genotype-phenotype correlation in patients with GSD 0a. Conclusion: This is a clinical report of a Japanese GSD 0a patient with novel GYS2 mutations and a review of cases. As secondary hepatic disorders may occur due to postprandial hyperglycemia, the treatment's ultimate goal is to prevent both hypoglycemia and hyperglycemia.